Effect of Porous and Nonporous Nanostructures on the Permeance of Positively Charged Nanofilm Composite Membranes. Issue 19 (9th August 2020) - Sarkar, Pulak; Modak, Solagna; Karan, Santanu
Abstract: The role of the nanostructured materials incorporated in the separation layer of thin‐film composite membranes is not properly understood yet, as it requires stringent salt rejection values, proper imaging of the separation layer to realize the presence of nanostructured materials, and to know the thickness of the separation layer. Here, the scalable fabrication of high flux positively charged "polyamide composite nanofiltration" membranes with an ultrathin nanofilm separation layer of ≈14 nm produced via interfacial polymerization of polyethyleneimine and trimesoyl chloride is presented. "Polyamide nanocomposite nanofiltration" membranes are fabricated with the incorporation of different porous and nonporous nanostructures (e.g., ZIF‐8, TiO2, and Fe2 O3 nanoparticles, graphene oxide, multi‐walled carbon nanotube, etc.) within the nanofilm separation layer. High water permeance of 15.4 L m −2 h −1 bar −1 (an increase of 33.9% compared to the pure nanofilm) is achieved with high rejection of MgCl2 (97.6%). Such membranes with enhanced water permeance surpass the upper bound of the permeance‐rejection of the state‐of‐the‐art positively charged nanofiltration membranes applicable for ionic and molecular separation. Abstract : Nanofiltration performance of the polyamide nanocomposite membranes fabricated via interfacial polymerization of polyethyleneimine and trimesoyl chloride with the incorporation of different porous and nonporous nanostructures within the nanofilm separation layer is studied. High water permeance of 15.4 L m −2 h −1 bar −1 (an increase of 33.9% compared to the pure nanofilm) with a high rejection of MgCl2 (97.6%) for MWCNT incorporated membranes is demonstrated.